Peningkatan Motivasi dan Penerimaan Keluarga dalam Merawat Pasien GGK dengan Terapi Hemodialisa melalui Supportive Educative Group Therapy - Dhina Widayati; Nian Afrian Nuari; Joko Setyono (Politeknik Kesehatan Tanjung Karang, 2018)
Patients with chronic renal failure (CRF) are terminal patients who require hemodialysis therapy to sustain life and improve their quality of life. Decrease in motivation and acceptance of the family will affect the patient, so that intervention is needed to increase motivation and family acceptance, one of which can be done through supportive educative group therapy. The purpose of this study was to determine the effect of supportive educative group therapy on motivation and family acceptance in caring for CRF patients with hemodialysis therapy. This research used Pre-Experimental design with one-group pre-post test design. Sample consists of 30 respondents picked up with Accidental sampling technique. Supportive Educative group therapy interventions for 45 minutes each session, consisting of 4 sessions and conducted in 2 meetings in 1 week. Before intervention supportive educative group therapy some respondents have motivation in the low category and acceptance in the category enough. After the intervention given the majority of respondents have motivation and acceptance in the high category. The data obtained in the analysis using the statistical test Wilcoxon sign rank test, with p-value=0.005 (motivation) and p-value=0.001 (family acceptance), α=0,05 and p<α. The result of research showed there influence educative group therapy to motivation and family acceptance in treating patients with chronic renal failure who undergo hemodialysis therapy. Recommendations on the Hemodialisa RS unit can be able to apply supportive educative group therapy as a specialist therapy to provide comprehensive family nursing care and nursing services.